Persamaan Lorenz untuk Keamanan Nomor Serial Sistem Operasi Window7 - Dewanto Harwin Rohan; Nur Hayati (Jurnal Ilmiah FIFO, 2018)
Serial number of operating system windows 7 needs to be safeguarded, so can’t be used by the others. Security of the data can use by modern cryptography such as Vernam Cipher methods and classic cryptography such as Caesar Cipher methods. The security level both of this method depends on the keywords used and it will difficult to crack if the random key is used more and more. To get a random key, we can take from chaos of Lorenz equations as key-generator for encryption and description. Before utilizing chaos in the Lorenz equations, we have to find the maximum t (time) for the inverse problem solution to fit with the forward problem solution. We can use Runge-Kutta method in the Lorenz equations for forward problem solution and inverse problem solution. The solution of integral that obtained by the Runge-Kutta method can be searched by Trapezoidal method. The result of Runge-Kutta solution and Trapezoidal will be used as key-generator for encryption and description. In the simulations performed, the best orde in Runge-Kutta method is 4 and t max is 2. The encryption key is used as the initial condition of Lorenz equation, then the result is integrable by the Trapezoidal method. The result of orde 4 from Runge-Kutta method and Trapezoidal method used as a key-generator.  Application of Lorenz equation as key-generator for encryption and decryption, may change the cryptography algorithms of symmetric to be asymmetric.